1995
DOI: 10.1038/ki.1995.472
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of antibody-mediated glomerular injury in vivo by IL-1ra, soluble IL-1 receptor, and soluble TNF receptor

Abstract: The severity of glomerular injury in the heterologous phase of NTN is dependent on proinflammatory cytokines including TNF alpha and IL-1 beta, and can be enhanced by LPS. We have previously shown that passive immunization against IL-1 beta and TNF partially abrogated the LPS effect in this model. In the present work, we have assessed the effects on glomerular injury of blocking and binding of IL-1 to its receptor by rh IL-1 receptor antagonist (IL-1ra) and by neutralizing IL-1 and TNF with rm soluble IL-1 rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 45 publications
3
36
0
Order By: Relevance
“…Inhibition of TNF resulted in a significant inhibition of renal injury, as shown by a >50% reduction in urinary albumin: creatinine ratio (Fig. 7C), consistent with previously published results in similar models (31,32). Similarly, inhibition of CXCL1 also resulted in a significant reduction in urinary albumin: creatinine ratio (Fig.…”
Section: Tnf Is Up-regulated In Monocytes In the Inflamed Kidney Andsupporting
confidence: 80%
See 1 more Smart Citation
“…Inhibition of TNF resulted in a significant inhibition of renal injury, as shown by a >50% reduction in urinary albumin: creatinine ratio (Fig. 7C), consistent with previously published results in similar models (31,32). Similarly, inhibition of CXCL1 also resulted in a significant reduction in urinary albumin: creatinine ratio (Fig.…”
Section: Tnf Is Up-regulated In Monocytes In the Inflamed Kidney Andsupporting
confidence: 80%
“…Of these mediators, TNF has been previously identified as a critical mediator in in situ immune complexmediated glomerulonephritis, via its promotion of adhesion molecule expression and glomerular barrier breakdown (31,32). TNF is also a potent and rapid inducer of ROS production via stimulation of NAPDH oxidase activity in neutrophils (39), a pathway we have previously shown to be responsible for glomerular dysfunction in acute glomerular inflammation (20).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in murine crescentic glomerulonephritis (GN) indicate that IL-1β is the major proinflammatory cytokine-mediating glomerular injury [20]. The benefits of inhibiting IL-1 using anti-IL-1 antibodies [21], soluble IL-1 receptor, or IL-1-receptor antagonist [22] have been shown in experimental GN. Our data revealed that increasing IL-1β expression accompanied severe glomerulosclerosis and renal tubular cell injury in untreated ADR-nephrosis rats, whereas mild and moderate glomerulosclerosis and renal tubular cell injury with weak IL-1β expression were found in the renal tissue of simvastatin-treated ADR-nephrosis rats.…”
Section: Discussionmentioning
confidence: 99%
“…In experimental GN, administration of soluble TNF receptors to rats developing crescentic GN reduced glomerular injury and prevented crescent formation (4,5). Anti-TNF antibodies (Ab) attenuate acute heterologous phase antiglomerular basement membrane (GBM) Ab-induced injury in rats (3).…”
mentioning
confidence: 99%